Evolutionist Humanism of Muhammad Iqbal: Response to Sartre’s Existentialism - Fadel, Achmad; Ruhani, Mahdi; Hamdani, Basrir (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2024)
The differences in the foundational thoughts on humanity become a factor in the plurality of interpretations of humanism that seeks to interpret ideal humanity. Jean Paul Sartre proposed a typical existentialist humanism, which removes the essence from humanity. Humans are left without meaning with the freedom to dynamically determine their own essence. The problem is that humans are only viewed from the aspect of freedom alone, while the aspects of evolution and human improvement are ignored. Therefore, by using the evolutionary humanism perspective of Muhammad Iqbal, humans are allowed to have the freedom to determine their essence while simultaneously perfecting themselves towards the absolute source of existence in the universe. The purpose of this research is to respond to Sartre's freedom humanism using Iqbal's evolutionary humanism with a descriptive analysis approach. The research results show that Sartre's humanism places freedom as the goal, while Iqbal makes freedom an instrument to achieve perfection (absolute ego). Sartre's disregard for freedom nullifies morality and the values of civilization considered important by humanism. Therefore, evolution is a key element for freedom, humanism, and civilization that can contribute to the foundation of ethics and culture